Regorafenib-loaded poly (lactide-co-glycolide) microspheres designed to improve transarterial chemoembolization therapy for hepatocellular carcinoma - Xiang Li; Guangwei He; Feng Su; Zhaoxing Chu; Leiming Xu; Yazhong Zhang; Jianping Zhou; Yang Ding (Elsevier, 2020)
Transarterial chemoembolization (TACE) has been widely introduced to treat hepatocellular carcinoma (HCC) especially for unresectable patients for decades. However, TACE evokes an angiogenic response due to the secretion of vascular endothelial growth factor (VEGF), resulting in the formation of new blood vessels and eventually tumor recurrence. Thus, we aimed to develop regorafenib (REGO)-loaded poly (lactide-co-glycolide) (PLGA) microspheres that enabled localized and sustained drug delivery to limit proangiogenic responses following TACE in HCC treatment. REGO-loaded PLGA microspheres were prepared using the emulsion-solvent evaporation/extraction method, in which DMF was selected as an organic phase co-solvent. Accordingly, we optimized the proportion of DMF, which the optimal ratio to DCM was 1:9 (v/v). After preparation, the microspheres provided high drug loading capacity of 28.6%, high loading efficiency of 91.5%, and the average particle size of 149 µm for TACE. IR spectra and XRD were applied to confirming sufficient REGO entrapment. The in vitro release profiles demonstrated sustained drug release of microspheres for more than 30 d To confirm the role of REGO-loaded microspheres in TACE, the cell cytotoxic activity on HepG2 cells and anti-angiogenic effects in HUVECs Tube-formation assay were studied in combination with miriplatin. Moreover, the microspheres indicated the potential of antagonizing miriplatin resistance of HepG2 cells in vitro. Pharmacokinetics preliminary studies exhibited that REGO could be sustainably released from microspheres for more than 30 d after TACE in vivo. In vivo anti-tumor efficacy was further determined in HepG2 xenograft tumor mouse model, demonstrating that REGO microspheres could improve the antitumor efficacy of miriplatin remarkably compared with miriplatin monotherapy. In conclusion, the obtained REGO microspheres demonstrated promising therapeutic effects against HCC when combined with TACE.